2000
DOI: 10.1002/1097-4636(20000905)51:3<475::aid-jbm23>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics

Abstract: Osteoblast, fibroblast, and endothelial cell adhesion on nanophase (that is, materials with grain sizes less than 100 nm) alumina, titania, and hydroxyapatite (HA) was investigated using in vitro cellular models. Osteoblast adhesion was significantly (p < 0.01) greater after 4 h on nanophase alumina, titania, and HA than it was on conventional formulations of the same ceramics. In contrast, compared to conventional alumina, titania, and HA, after 4 h fibroblast adhesion was significantly (p < 0.01) less on nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
578
4
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 938 publications
(613 citation statements)
references
References 22 publications
(19 reference statements)
24
578
4
7
Order By: Relevance
“…A previous study has demonstrated that FN was not involved in the adhesion of osteoblasts to uncoated Ti alloy at 24 h [25]. Moreover, the integrin a 5 Fwhich is a major adhesion receptor of osteoblasts interacting with FN [26,27]Fwas not detected in cell cultured on polished or rough Ti-6A1-4V at 12 h while it was detected for cell cultured on polystyrene [28]. Despite results of the study by Sinha and Tuan [28] were obtained at 12 h while present FN results were obtained at week 1, they could support the hypothesis that proteins other than FN were involved in the osteoblast adhesion to Ti alloy.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study has demonstrated that FN was not involved in the adhesion of osteoblasts to uncoated Ti alloy at 24 h [25]. Moreover, the integrin a 5 Fwhich is a major adhesion receptor of osteoblasts interacting with FN [26,27]Fwas not detected in cell cultured on polished or rough Ti-6A1-4V at 12 h while it was detected for cell cultured on polystyrene [28]. Despite results of the study by Sinha and Tuan [28] were obtained at 12 h while present FN results were obtained at week 1, they could support the hypothesis that proteins other than FN were involved in the osteoblast adhesion to Ti alloy.…”
Section: Discussionmentioning
confidence: 97%
“…2 is not frequently measured, especially the early attachment phase characterized by t 1/2 and %I max, because cell-enumeration protocols are quite labor intensive (there are a variety of cell-enumeration methods available including dye techniques [67][68][69][70][71][72][73][74], autoradiography [75], light and electron microscopy [76][77][78], Coulter counting [79], hemocytometry [80], spectrometry [81,82], nuclei number [83], total DNA [84], total protein concentration [78,85] that may or may not give similar results, depending on cell number and specific experimental conditions). Instead, a variety of experimental shortcuts are taken, such as measuring attached-cell-number after some arbitrary cell-surface contact time [86][87][88][89].…”
Section: Cell Attachment and Proliferation Kineticsmentioning
confidence: 99%
“…The reduction in cell number seen on composite matrices may also be due to limited spreading of cells on the calcium phosphate surface. Other studies have shown limited colony occupancy of osteoblasts cultured on nanophase ceramics including hydroxyapatite [9]. According to x-ray diffraction patterns of the calcium phosphate formed within the composite matrices, there is good evidence that the calcium phosphate formed is nanophase hydroxyapatite [6].…”
Section: Percent Ca 2 + Of Simulated Body Fluidmentioning
confidence: 99%